A Systematic Review of the Benefits and Challenges Associated with the Hybrid Collaboration of Cloud with Specific Reference to Small and Medium Businesses (SMBS) (Global Journal of Management and Business Research, 2017)
There has been an Upsurge in the use of Cloud Services in Businesses and Small and Medium Sized Enterprises are using Software Services as well as Infrastructure Services Provided by Professional Information Service Companies. These Companies Provide the Msmes (Micro, Small and Medium Scale Enterprises) with Services Such as Data Storage, Document Sharing, E-Mail Domains, and Other Computer as well as Management Information Systems as Public Resources in Order to Support their Business Processes Management. However, There is a Limitation in the Services One Vendor can Supply and Thus These Businesses need to Simultaneously use Services from Different it Platforms and Conduct their Business. Cloud, Called as the ‘Future of Information Technology’, Plays a Crucial Role in this Regard. Hybrid Collaboration of Cloud, In Simple Words can be Explained as the Integration of Public and Private Cloud Services. The Purpose of this Study is to Summarize with a Systematic Review, The Previous Researches on Hybrid Collaborations in Cloud and How Msmes use these Applications for their Benefit.
Keywords: cloud computing; hybrid; business; management; collaborations; communication